Finding the Balance: Embracing the Two-Eyed Seeing Approach to Understand what Cultural Safety in Care Means to Older Adults Living with HIV. (September 2022) - Vorobyova, Anna; Marante, Antonio; Cardinal, Claudette; Magagula, Patience; Lyndon, Sharyle; Braley, McKenzie; Inglis, Kathleen; Parashar, Surita
Older adults living with HIV (OALHIV) are a fast-growing demographic who rely on home and community care (HCC) services. Cultural safety (an environment free of racism that fosters feelings of safety and respect) is integral to HCC services. We conducted 27 semi-structured interviews with OALHIV in Vancouver, British Columbia about their HCC experiences. Excerpts about cultural safety were qualitatively analyzed using Two-Eyed Seeing. Our themes—Voices from across Turtle Island, Voices from the African continent, Western Perspectives, and Universal Principles—indicate that cultural safety is important yet lacking. While specific aspects of culturally safe HCC services varied between and within cultural groups, some aspects were shared by participants across groups (e.g., respect, compassion, and non-judgment).